Peningkatan Produktivitas Domba pada Skala Peternakan Rakyat Melalui Pemberian Hormon Pregnant Mare Serum Gonadotrophin (IMPROVEMENT OF SMALL HOLDER FARMS SHEEP PRODUCTIVITY THROUGH THE APPLICATION OF PREGNANT MARE SERUM GONADOTROPHIN) - ., Andriyanto; Manalu, Wasmen (Jurnal Veteriner; Vol 13 No 3 (2012), 2013)
The administration of Pregnant Mare Serum Gonadotrophin (PMSG) hormone to stimulate superovulation has been proven to improved fetal prenatal growth, birth weight, mammary gland growth anddevelopment, milk production, litter size, as well as pre and post weaning growth. This study was conductedto apply the administration of PMSG hormone technology in small-holder farms. One hundred ewes weredivided into two groups. Group I (control: 50 ewes) ewes without administration of PMSG and Group 2(treatment: 50 ewes) ewes with administration of PMSG to stimulate super ovulation and improveendogenous secretion of pregnant hormones. The application of PMSG increased the numbers of lamb bornby 26.8% (69 vs. 87) with average litter size of 20.7% (1.38 vs. 1.74). The lamb weight at birth was alsoincreased by 25.7% (2.76 ± 0.33 vs. 3.47 ± 0.35 kg). The milk production of the dam was also increased by29.7% (0.64 ± 0.25 vs. 0.91 ± 0.22 L/ewe/day). Lambs born to ewes administered PMSG had better weaningweight 22.1% (12.32 ± 2.44 vs. 15.04 ± 1.11 kg/ewe). The number of survival lamb to reach weaning age washigher compared to the control group. The weight at weaning age was almost twice (628.4 kg vs. 1202.8 kg)compared to the control group. Using simple economic analysis calculation, the application of this hormonetechnology could increase gross revenue by Rp 294.280- per ewes. It was concluded that the administrationof PMSG is economically feasible to be applied in to the small-holder farms.
Keywords: PMSG hormone, productivity, ewes, small-holder farms